Near‐surface permafrost extent and active layer thickness characterized by reanalysis/assimilation data - Zequn Liu; Donglin Guo; Wei Hua; Yihui Chen (Atmospheric Science Letters)
Abstract Whilst permafrost change is widely concerned in the context of global warming, lack of observations becomes one of major limitations for conducting large‐scale and long‐term permafrost change research. Reanalysis/assimilation data in theory can make up for the lack of observations, but how they characterize permafrost extent and active layer thickness remains unclear. Here, we investigate the near‐surface permafrost extent and active layer thickness characterized by seven reanalysis/assimilation datasets (CFSR, MERRA‐2, ERA5, ERA5‐Land, GLDAS‐CLSMv20, GLDAS‐CLSMv21, and GLDAS‐Noah). Results indicate that most of reanalysis/assimilation data have limited abilities in characterizing near‐surface permafrost extent and active layer thickness. GLDAS‐CLSMv20 is overall optimal in terms of comprehensive performance in characterizing both present‐day near‐surface permafrost extent and active layer thickness change. The GLDAS‐CLSMv20 indicates that near‐surface permafrost extent decreases by −0.69 × 106 km2 decade−1 and active layer deepens by 0.06 m decade−1 from 1979 to 2014. Change in active layer is significantly correlated to air temperature, precipitation, and downward longwave radiation in summer, but the correlations show regional differences. Our study implies an imperative to advance reanalysis/assimilation data's abilities to reproduce permafrost, especially for reanalysis data.